The Role of Parents in Teaching Islamic Values - Alfaruq, M. Ammar; Salsabila, Alin Nur; Tazhfira, Umriha (Jurnal Indonesia Sosial Sains, 2026)
The Role of Parents in Teaching Islamic Values to Children Parents play a very important role in educating and shaping children's character. Through the teaching of Islamic values carried out from an early age, parents can help children understand religious teachings and build a noble personality. The role of parents is not only as providers of physical needs but also as the main educators in shaping children's morals. By getting used to religious practices at home, such as performing ṣalāh (prayer), reading the Qur’an, making duʿāʾ (supplication), and demonstrating noble morals, parents can teach positive habits to their children. Through consistent examples, children will imitate these behaviors and understand the importance of Islamic values in daily life. According to several sources, the teaching of Islamic values carried out by parents from an early age will have a positive impact on the development of children's character. This also helps children understand the basic principles of Islam, such as honesty, concern for others, and respect for the commands of Allah SWT. In addition, good communication between parents and children is also an important means of this teaching. Parents need to listen to their children's concerns, discuss daily life, and provide simple but meaningful explanations of religious principles.